PP31 Ambulance handover: a thematic review of delays in 2018/19. Issue 10 (25th September 2020) - Lindridge, Jaqualine; Reynard, Kevin; Kemp, Rob; Brownhill, Richard; Penn-Ashman, Jerry
Abstract : Background: Ambulance handover delays are an important indicator of an emergency care system under pressure. Delayed handovers compromise patient safety in the Emergency Department (ED). As a direct consequence patients wait longer for an emergency ambulance response, and as a result patient safety in the community is also compromised. We explored factors perceived to contribute to ambulance handover delays at EDs in an urban area of England, in order to inform delay reduction strategies. Methods: Fifteen EDs were visited as part of a regional improvement programme. Ambulance handover processes were observed, and staff involved in the process were informally interviewed. A data corpus of twenty-nine written reports was generated. These reports were anonymised and thematic analysis was used inductively to explore the phenomenon of ambulance handover delay. Pattern coding was used to identify and cluster common themes, with magnitude coding added to identify the most prevalent themes. Results: Perceived reasons for ambulance handover delay arose from a number of factors. A mismatch was frequently seen between handover capacity and demand. This occurred alongside, but was also frequently observed to be independent of, ED exit block. Approaches to escalation were often sub-optimal. This was observed both before and after an ambulance queue developed. Processes were often uneconomical by design, and pathways were frequently inefficient. Inter-professional culture was identified as an important, cross-cutting theme, with a lack of urgency to release ambulances frequently observed. Conclusions: Our results suggest several factors influence ambulance handover delays. Programmes which aim to improve overall hospital flow, streamline pathways and processes, and improve escalation are needed. Programmes should also seek to improve the inter-professional culture relating to ambulance handover. Limitations to this enquiry include an opportunistic, retrospective approach and use of a convenience sample. There are few empirical studies which address the causes of ambulance handover delay. More research is needed on this important patient safety issue.